Management of incus long process defects: incus interposition versus incudostapedial rebridging with bone cement - (:unkn) unknown (CAMBRIDGE UNIV PRESS, 2013)
Objective: This study aimed to compare the hearing results of incus interposition and bone cement ossiculoplasty in patients with incus long process defects. Materials and methods: Ninety-nine patients with incus long process defects were included. Incus interposition was performed in 49 patients (group 1) and bone cement ossiculoplasty was performed in 50 patients (group 2). Group 1 included 29 female and 20 male patients, with a mean age +/- standard deviation of 29.43 +/- 12.5 years (range, 8-58 years). Group 2 comprised 32 female and 18 male patients, with a mean age +/- standard deviation of 29.1 +/- 14.89 years (range, 8-67 years). Results: The mean hearing gain +/- standard deviation was 15.2 +/- 9.01 dB in group 1 and 19.36 +/- 9.08 dB in group 2. Hearing gain was significantly greater in the bone cement group than in the incus interposition group (p = 0.0186). Successful hearing results (i.e. air-bone gap < 20 dB) were achieved by 63.2 per cent of group 1 patients and 78 per cent of group 2 patients. Conclusion: Incus interposition and bone cement ossiculoplasty are safe and reliable methods with which to manage incus long process defects. Bone cement ossiculoplasty gives a greater hearing gain in appropriate cases.
Keywords: Incus; Bone Cements; Ossicular Replacement; GLASS-IONOMER CEMENT; MIDDLE-EAR; OSSICULAR CHAIN; OSSICULOPLASTY; RECONSTRUCTION; TITANIUM; STAPES